Benzo[1, 2‐b:4, 5‐b′]difuran Based Polymer Donor for High‐Efficiency (>16%) and Stable Organic Solar Cells. Issue 9 (13th January 2022) - Li, Xiaoming; Duan, Xiaopeng; Liang, Zezhou; Yan, Lihe; Yang, Yinuo; Qiao, Jiawei; Hao, Xiaotao; Zhang, Chen; Zhang, Jie; Li, Yan; Huang, Fei; Sun, Yanming
Abstract: Molecular design of polymer donors is of vital importance for obtaining high‐performance organic solar cells (OSCs). At present, much of the important progress in power conversion efficiencies (PCEs) achieved for OSCs has been associated with the benzodithiophene (BDT)‐based polymers, while the highest PCE of benzo[1, 2‐b:4, 5‐b′]difuran (BDF) polymer‐based OSCs only reaches 14.0%. Here, a polymer donor named PBDF‐NS is designed and synthesized by using naphthalene‐substituted benzo[1, 2‐b:4, 5‐b′]difuran as the electron‐sufficient units and fluorinated benzotriazole (BTz) as the electron‐deficient units. PBDF‐NS possesses a low‐lying HOMO level of −5.44 eV and a wide bandgap of 1.87 eV. When using LC301 as the acceptor, PBDF‐NS‐based OSC exhibits an excellent PCE of 15.24%. Moreover, the ternary and all‐polymer devices based on PBDF‐NS both achieve a higher PCE over 16%, which represents the highest efficiency values reported for BDF polymer‐based OSCs in the literature thus far. Meanwhile, the binary and ternary devices all display excellent storage and light‐soaking stabilities. The results demonstrate that by rational molecular design, BDF‐based copolymers can be comparable to or even surpass the performance of BDT‐based counterparts and also show great potential for realizing high‐efficiency all‐polymer solar cells. Abstract : A polymer donor PBDF‐NS is synthesized by using naphthalene‐substituted benzo[1, 2‐b:4, 5‐b′]difuran (BDF) and fluorinated benzotriazole units. PBDF‐NS possesses a low‐lying HOMO level of −5.44 eV and a wide bandgap of 1.87 eV. Enormous progress in efficiency are achieved from 14% to over 16%, which are the highest efficiencies for BDF copolymer‐based organic solar cells.